High Temperature Induces Expression of Tobacco Transcription Factor NtMYC2a to Regulate Nicotine and JA Biosynthesis - Yang, Liming; Li, Junying; Ji, Jianhui; Li, Ping; Yu, Liangliang; Abd_Allah, Elsayed F.; Luo, Yuming; Hu, Liwei; Hu, Xiangyang (Frontiers in Physiology, 2016)
Environmental stress elevates the level of jasmonic acid (JA) and activates the biosynthesis of nicotine and related pyridine alkaloids in tobacco (Nicotiana tabacum L.) by up-regulating the expression of putrescine N-methyltransferase 1 (NtPMT1), which encodes a putrescine N-methyl transferase that catalyzes nicotine formation. The JA signal suppressor JASMONATE ZIM DOMAIN 1 (NtJAZ1) and its target protein, NtMYC2a, also regulate nicotine biosynthesis; however, how these proteins interact to regulate abiotic-induced nicotine biosynthesis is poorly understood. In this study, we found that high-temperature (HT) treatment activated transcription of NtMYC2a, which subsequently stimulated the transcription of genes associated with JA biosynthesis, including Lipoxygenase (LOX), Allene oxide synthase (AOS), Allene oxide cyclase (AOC), and 12-oxophytodienodate reductase (OPR). Overexpression of NtMYC2a increased nicotine biosynthesis by enhancing its binding to the promoter of NtPMT1. Overexpression of either NtJAZ1 or proteasome-resistant NtJAZ1∆C suppressed nicotine production under normal conditions, but overexpression only of the former resulted in low levels of nicotine under HT treatment. These data suggest that HT induces NtMYC2a accumulation through increased transcription to activate nicotine synthesis; meanwhile, HT-induced NtMYC2a can activate JA synthesis to promote additional NtMYC2a activity by degrading NtJAZ1 at the post-transcriptional level.